2006
DOI: 10.1002/ajmg.a.31538
|View full text |Cite
|
Sign up to set email alerts
|

A report of pure 7p duplication syndrome and review of the literature

Abstract: We report on a case of a 9-month-old female infant with a direct duplication of the 7p13-p22.1 chromosome region diagnosed by combining conventional cytogenetic, FISH, and multicolor banding (MCB) studies. Traditional G-banding detected a partial 7p duplication, which was further demonstrated to be entirely of chromosome 7 origin by using a whole chromosome paint for chromosome 7, and derived from 7p13-p22.1 by MCB. The infant presented with characteristic dysmorphic features, psychomotor retardation, and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
(55 reference statements)
1
29
0
1
Order By: Relevance
“…In humans, duplication of a limited number of genes has been found to be associated with disease. For example, duplication of the SNCA gene, which encodes a-synuclein, leads to early onset Alzheimer's disease (reviewed in Farrer 2006); duplication of PMP22 leads to Charcot-Marie-Tooth 1A (CMT1A) neuropathy (reviewed in Hanemann and Muller 1998); and duplication of a fragment of the short arm of chromosome 7 (7p13-p22.1) causes severe developmental abnormalities (Papadopoulou et al 2006).…”
Section: Why Does Aneuploidy Reduce Organismal Fitness?mentioning
confidence: 99%
“…In humans, duplication of a limited number of genes has been found to be associated with disease. For example, duplication of the SNCA gene, which encodes a-synuclein, leads to early onset Alzheimer's disease (reviewed in Farrer 2006); duplication of PMP22 leads to Charcot-Marie-Tooth 1A (CMT1A) neuropathy (reviewed in Hanemann and Muller 1998); and duplication of a fragment of the short arm of chromosome 7 (7p13-p22.1) causes severe developmental abnormalities (Papadopoulou et al 2006).…”
Section: Why Does Aneuploidy Reduce Organismal Fitness?mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Common features include craniofacial anomalies, a large fontanelle, dysmorphism and psychomotor delay, with hypotonia being the most common complication observed. [1][2][3][4][5][6][7][8]10,11,13 In their review of the literature, Cai et al found that 50% of 7p duplications were the result of balanced reciprocal translocation carriers. 3 Reish et al suggested that these could be an entire duplication duplication.…”
Section: Discussionmentioning
confidence: 99%
“…1 Chui et al reported a patient with microduplication at 7p22. 1 (1.7 Mb) who showed all of the common craniofacial features and had cryptorchidism, but did not have global developmental delay or hypotonia.…”
Section: Discussionmentioning
confidence: 99%
“…The duplication of the short arm of chromosome 7 causes a characteristic pattern of malformations including developmental, craniofacial, skeletal, and cardiovascular anomalies, the severity of which depends on the size of the duplication [Papadopoulou et al, 2006]. The neuronal migration defect could be explained by the deletion of CDON (cell adhesion molecule-related/ downregulated by oncogenes, MIM 608707) and KIRREL3 (Kin of IRRE-like 3, MIM 607761) on chromosome 11, which are 2 genes involved in the control of neuronal migration and axon guidance [Okada et al, 2006;Bhalla et al, 2008].…”
Section: Resultsmentioning
confidence: 99%